Development of Sipejar Content with Accessibility of Students with Special Needs in Coursesassessment of Children with Special Needs - Dewantoro, Dimas Arif; Pradipta, Rizqi Fajar; Kurniawan, Citra; Hanif, Ellora Fauziyyah (Universitas Negeri Malang, 2024)
The Assessment Course for Children with Special Needs is one of the compulsory and crucial courses for special education students. So far the Development of Learning Design and learning objects has not accommodated students with special needs, especially students. Therefore, this research will develop content that accommodates students who have hearing impairments with micro-learning-based content. The development of micro learning content is carried out through a series of stages of research and development. The development design used was the Davidson-Shiver and Rasmunssen development model. In general, the Davidson-Shiver and Rasmussen models are development methods that have dominant characteristics in web-based development. This research will produce teaching content in the Disability-friendly Assessment of Children with Special Needs Course. From the results obtained the details of the content needed as follows: Textbook 96.18%, PPT 95.54%, Ebook 94.90%, Video 91.72%, Video Podcast 63.69%, Audio Podcast 33.76% and Audiobook 22.93%. So it can be concluded that more content is needed is Textbooks and PPT or Presentation Slides.